Les écoles publiques alternatives du Québec : description écosystémique par croisement des expériences vécues d’anciens élèves et d’acteurs actuels - Philippe Chaubet; François Bissonnette; Vicky Lachance; Jasmin Beauclair; Akâsha Fadoul (Recherches en Éducation)
The article aims at the ecosystem description of the 48 schools in the network of alternative public schools of Quebec (RÉPAQ), based on the positive stories of the experiences of former students and current actors. To understand their common functioning from an outside eye, we voluntarily put aside the discourse and vocabulary of their internal documents and interviewed actors with diverse roles in 14 of these schools: teachers, management, educational advisors, parents, daycare providers, former students. The triangulation of points of view reveals regularities of lived experiences, a whole coherent ecosystem of postures and functioning. This particular school form appears to be based on a reassuring and motivating framework, which creates, in action, mutual respect, all ages and roles combined. The relationship to knowledge seems to be a relationship to curiosity, to daring, to the art of investigating to understand, a taste for learning. The methodology is qualitative and comprehensive. The approach is phenomenological: identifying the phenomena at work as closely as possible to the experiences of the participants, while respecting their perceptions.